2020
DOI: 10.1126/scitranslmed.aax9340
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell protein kinase C-β inhibition enhances chemosensitivity in B cell malignancies and overcomes drug resistance

Abstract: Overcoming drug resistance remains a key challenge to cure patients with acute and chronic B cell malignancies. Here, we describe a stromal cell–autonomous signaling pathway, which contributes to drug resistance of malignant B cells. We show that protein kinase C (PKC)–β–dependent signals from bone marrow–derived stromal cells markedly decrease the efficacy of cytotoxic therapies. Conversely, small-molecule PKC-β inhibitors antagonize prosurvival signals from stromal cells and sensitize tumor cells to targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 70 publications
2
30
0
Order By: Relevance
“…Idelalisib or duvelisib also reduced the ability of stromal cells to support CLL migration and adhesion (161); (d) finally, targeting the over-expression of BCL2 partially induced by the microenvironment has also been proposed (163,164). adhesion and matrix proteins, required for activation of PI3Ks and ERK-mediated stabilization of BCL-XL in tumor cells (162). Microenvironment stimuli provided during CLL/MSC coculture lead to the increase of BCL2 through Notch-1, Notch-2, Notch-4 signaling (97).…”
Section: Targeting Cll/msc Crosstalkmentioning
confidence: 99%
See 2 more Smart Citations
“…Idelalisib or duvelisib also reduced the ability of stromal cells to support CLL migration and adhesion (161); (d) finally, targeting the over-expression of BCL2 partially induced by the microenvironment has also been proposed (163,164). adhesion and matrix proteins, required for activation of PI3Ks and ERK-mediated stabilization of BCL-XL in tumor cells (162). Microenvironment stimuli provided during CLL/MSC coculture lead to the increase of BCL2 through Notch-1, Notch-2, Notch-4 signaling (97).…”
Section: Targeting Cll/msc Crosstalkmentioning
confidence: 99%
“…Complementarily, idelalisib or duvelisib also significantly reduced the ability of stromal cells to support CLL migration and adhesion ( 161 ). Another way to disrupt CLL/MSC crosstalk and overcoming drug resistance in CLL patients is to directly target PKC-β signaling pathway in MSC: indeed, Park et al showed that small-molecule PKC-β inhibitors antagonize prosurvival signals from stromal cells and sensitize tumor cells to targeted and non-targeted chemotherapy, resulting in enhanced cytotoxicity ( 162 ). In addition, they also showed that stromal PKC-β controls the expression of adhesion and matrix proteins, required for activation of PI3Ks and ERK-mediated stabilization of BCL-XL in tumor cells ( 162 ).…”
Section: Targeting Cll/msc Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrates the importance of PKCβ expression in the stromal compartment to protect malignant Bcells from cytotoxic therapies in vivo enrolling a PKCβ-dependent effect in environment-mediated drug resistance of CLL cells. 47,48 Therefore, induced expression of PKCβ may be a common mechanism of malignant cells to harness stromal cells for tumorpromoting purposes. Here, we show that the expression of stromal PKCβ results in metabolic changes and altered ROS production in BMSC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the resistance of CLL cells toward drug-induced apoptosis is also mediated by stromal contact, clinically recognized as a minimal-residual disease (MRD) [5]. Recently, in vivo experiments demonstrated that the inhibition of PKCb in stromal cells enhances chemosensitivity in CLL and overcomes drug resistance [6]. It could be shown that stromal contact activates Notch signaling [7] indicating that Notch might play a distinct role in the communication between CLL cells and the microenvironment.…”
Section: Introductionmentioning
confidence: 99%